Gold nanoclusters with a wide range of fluorescence characteristics generated in situ in polymer thin films: potential gas sensing application. Issue 46 (14th November 2017) - Divya Madhuri, U.; Radhakrishnan, T. P.
Abstract : Gold nanoclusters with variable emission characteristics are generated in situ in polymer films by mild thermal annealing and their potential application as gas detectors is demonstrated. Abstract : Fabrication of gold nanoclusters (GNCs) with tunable fluorescence characteristics inside polymer thin films is attractive from the device application perspective. In this study, GNCs are generated in situ in poly(methyl methacrylate) films exploiting their weak reducing capability with no additional reducing agent, and by short and mild thermal annealing; the chemistry involved is probed through control experiments. The nanoclusters formed with ∼0.5 weight percent of gold are very stable and show appreciable fluorescence emission with a small Stokes shift (∼40 nm); interestingly, blending polystyrene enhances the fluorescence. The Au10 clusters formed in situ are characterized by using mass spectrometry, microscopy and computational modeling. Composite thin films fabricated with a gold content of ∼9 weight percent showed an unusually distinct absorption peak and enhanced fluorescence emission. Gradual coalescence of the nanoclusters in these films could be arrested by incorporating thiourea; the mechanistic aspects of the thiourea interaction are probed. The resulting films showed strong, stable and visible red emission, with very large Stokes shift (∼320 nm) and quantum yield (∼30%), attributable to ligand effects and nanocluster aggregation in the film. The study presents a novel and facile route to the in situ generation of GNCs in polymer thin films, exhibiting fluorescence emission with variable energy, intensity and Stokes shift. Preliminary experiments show that Au10 cluster embedded thin films can be used for the detection of POCl3, an important precursor for nerve agents.